(untitled) (Research, Society and Development, 2022)
This research aims to show whether there are statistically significant mean differences between the predictive models of insolvency of Kanitz, Elizabetsky, Matias, Altman and Pereira in the civil construction sector of companies listed on the Brazilian stock exchange. Thus, the sector is composed of 21 companies, initially analyzed through descriptive statistics and correlation between the models and, finally, the use of analysis of variance to identify whether there are significant mean differences between the models. The results show that the Kanitz, Altman and Pereira Industry model presented solvency factors in the general average, the Elizabetsky model, insolvent, as well as the Matias and Pereira commercial models. The models showed statistically significant differences between them with three exceptions, that is, Elizabetsky versus Altman, Matias versus Pereira Industry and, finally, Pereira Industry versus Altman.